A Study on Academic Dishonesty and Moral Reasoning - Heriyati, Dina; Ekasari, Wulandari Fitri (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
Academic dishonesty in the form of cheating and plagiarism among university students has been a prevalent issue. This study investigates the role of moral reasoning as a moderator of fraud risk factors (Fraud Triangle - pressure, opportunity, and rationalization) on academic dishonesty. The data were collected through a survey of 178 undergraduate accounting students in one public university in Indonesia. The result of the partial least squares structural equation modeling analysis revealed that pressure, opportunity, and rationalization directly and positively affected academic dishonesty. The structural model was also examined across two groups based on the level of moral reasoning (Group 1: individuals with low moral reasoning; Group 2: individuals with high moral reasoning). The results showed that the pressure, opportunity, rationalization – academic dishonesty model remained invariant between the groups, a new finding contributed to the literature on academic dishonesty and the moderating effects of moral reasoning. The results of the study also suggest that university should uphold academic integrity by creating an environment where academic dishonesty is unacceptable and reduce the opportunity to commit dishonest acts because everybody might commit such acts regardless of their morality.